Sexism in @Lambeturah's Instagram Comments on Lisa Mariana: A Critical Discourse Analysis by Sara Mills - Tiara Mailani Abdillah; Angga Trio Sanjaya; Ririn Sulistyowati (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe forms of sexism in posts about Lisa Mariana’s latest appearance on Instagram @lambeturah through Sara Mills’ critical discourse analysis approach, reviewed from the perspective of the subject-object and reader’s position. This is based on the rampant discussion through negative comments on social media related to women who are victims of beauty construction and objectification based on their bad actions. The source of this research is netizen comments on posts on the Instagram account @lambeturah featuring Lisa Mariana’s latest appearance. The research method used is qualitative descriptive. The data collection method used the observation method with the advanced mote-taking technique.. Data analysis used the referential matching method with the basic technique of sorting determining elements (PUP). The results of this study show that there were 9 sexist comments and 6 reader responses to the sexist comments. Using Sara Mills subject-object and reader positions analysis model, the netizens who made sexist comments about Lisa Mariana were positioned as subjects who had the power to represent the object position or Lisa Mariana in a negative way, such as labeling, judging, defening, interpreting, evaluating, and interpreting Lisa Mariaa’s body, as well as determining what was appropriate to do in response to the affair. The reader’s position is divided between those who rejected sexism, reproduced sexism as a joke, and accepted sexism through body shaming practices.